Akrasia (swakheid van die wil) en die kontemporêre gesprek oor subjektiwiteit - Heyns, M. F. (Koers, 1997)
Akrasia (weakness of will) and the contemporary discourse on subjectivityThe issue about akrasia (weakness of the will) concerns the question whether the human will is strong enough to choose and realize actions, or whether a conflict, and a certain type of conflict (i.e. the issue of akrasia), will have the potential to paralyse it. My analysis focuses on ideas of thinkers of the last half of the twentieth century - thinkers like Skinner who practically denies the existence and strength of the se lf and Sartre who postulates a transcendental self with godlike capabilities. I conclude that both leave little room for the idea of akrasia. Akrasia needs a more subtle vision of the power and weakness of the self. To arrive at this conclusion I consider views attempting to reconcile the disempowerment of the se lf by the extra-self with the idea of a self in control of its situation. I argue that these views fail because they assume the akratic conflict to be behi’een the self and extra-self instead of an intra-will conflict. I also deny that the dialectic goal of a fusion o f the self and its situation will give an explanation o f the akratic conflict because dialectics still operate with a centred self which assumes a conflict between the centre and a sub-self periphery. Moreover, this kind of dialectics provides the picture of a permanent victimized self rather than an akratic conflict. I conclude by suggesting the existence of a "dense " self with more subjective capacities than is usually assumed. This, I argue, enhances the scope of, and makes the intra-will conflict more credible.